Employment, Knowledge and Latrine Ownership as Risk Factors and Prediction Model of Diarrhea Incidence - Irfan Irfan; Sulansi Sulansi (Intelektual Pustaka Media Utama, 2016)
Diarrhea is a leading cause of death ranked 3rd after Tuberculosis and Pneumonia in Indonesia. Diarrhea cases in NTT province and also in Kupang City is still high, with Pasir Panjang PHC in 2012 and 2013 ranked the top three, while Oepoi PHC always the lowest rank. This research was conducted to analyze the risk factors for the incidence of diarrhea and create a model equation to predict the diarrhea incidence. This observational analytic research using case control design. Samples with diarrhea cases were recorded in January - June 2015 in the register book Pasir Panjang PHC and Oepoi PHC taken by random sampling to obtain samples for cases 62 children of Diarrhea patient. The control samples are 62 children who are not registered as suffering from diarrhea in the month of June 2015, close to the patient’s house, and her mother or people who responsible to take care that children want as respondent. Data were obtained by interviews with the mothers of cases and controls using questionnaires and direct observation using a checklist. Data were analyzed using univariate, bivariate and multivariate logistic regression. There are three variables that significantly affect to the diarrhea incidence, namely employment, knowledge and latrine ownership and the most dominant variable influence that is knowledge (OR 4.353). The model equation Y = - 2.048 +1.153 employment + 1.483 knowledge + 1.480 latrine ownership with a percentage accuracy of the model in classifying observations is 68.5%.